Sod and GSH Inhibit the High Glucose-Induced Oxidative Damage and the PDGF Increased Secretion in Cultured Human Endothelial Cells - Curcio, Francesco; Pegoraro, Isabella; Russo, Patrizia Dello; Falleti, Edmondo; Perrella, Giusepplna; Ceriello, Antonio (Thrombosis and Haemostasis, 1995)
Poor control of blood glucose has been established as a key pathogenetic mechanism in the vascular complications of diabetes. It has been reported that glucose may autooxidize generating free radicals which have been suggested to delay proliferation, to modify mobility, to influence platelet-derived growth factor and other secretory protein production in a variety of cell systems. Platelet-derived growth factor, in turn, may induce proliferation and migration of vascular smooth muscle cells and thus play a role in atherogenesis. In the present study the effects of antioxidants on the high glucose-dependent oxidative cell damage and increased platelet-derived growth factor secretion have been investigated using cultured human endothelial cells. Our findings show that rising the glucose concentration in the culture medium from 5 mM to 20 mM, increased the production of free radicals cell damage markers, such as malondialdehyde and conjugated dienes, as well as the production of platelet-derived growth factor. The addition of superoxide dismutase or glutathione prevents both such effects. These results suggest that antioxidants may be a helpful therapeutic adjuvant to reduce the vascular complications of diabetes.